THE INFLUENCE OF EXPERIENTIAL MARKETING ON REPURCHASE INTENTION (STUDY AT MARASOE) - Reynaldi Eka Putra; Pratami Wulan Tresna; Cecep Safaatul Barkah; Arianis Chan (Journal of Business Studies and Management Review, 2021)
Marasoe is an online fashion business that sells women's products. In this era, the increasing number of fashion businesses makes Marasoe have to do experiential marketing to make a memorable experience for the consumer. A memorable experience will lead to a positive response, such as a repurchase intention. This research investigates the influence of experiential marketing on repurchase intention at Marasoe. This study uses quantitative research methods, and data gained using primary sources from questionnaires and secondary. The total sample involves 83 respondents who were selected by the purposive sampling technique. This study shows that experiential marketing has a significant influence on repurchase intention, either partially or simultaneously.